Sistem Informasi Penerimaan Siswa Baru Sma Islamic Centre Demak Berbasis Web mobile (Information Technology and Telematics, 2016)
Abstract : The information system as part of the development of information technology is needed to help performance. Structuring information that is regular, clear, precise, and fast. certainly strongly support the smooth operation that you want to develop applications in the manufacture of new admissions information system-based mobile web. Based on the above background boundary problem is "the design of the new Student Information System Web-based acceptance of mobile". The goal made this application is to present information on the system Admission to quickly and easily access it via Smartphone. The software used in the development of a new student information system SMA Demak Islamic Centre are: Adobe Photoshop,Dreamweafer, My SQL, Apache (2.2.4) + PHP (5.2.3) . Solutions are to be given the researchers is to design information systems are supported by a web-based mobile computer equipment. Keywords : Admission information systems, mobile web   Abstrak : Sistem informasi sebagai bagian dari perkembangan teknologi informasi sangat dibutuhkan untuk membantu kinerja. Penataan informasi yang dilakukan secara teratur, jelas, tepat, dan cepat.tentunya sangat mendukung kelancaran kegiatan yang ingin di kembangkan dalam pembuatan aplikasi sistem informasi penerimaan siswa baru berbasis web mobile.  Berdasarkan latar belakang diatas  batasan masalahnya adalah “perancangan Sistem informasi penerimaan Siswa baru Berbasis web mobile”. Tujuan dibuat aplikasi ini adalah menyajikan sistem informasi tentang Penerimaan Siswa Baru  dengan secara cepat & mudah mengakses nya melalui Smartphone. Perangkat lunak yang digunakan dalam pengembangan sistem informasi penerimaan siswa baru SMA Islamic Centre Demak adalah : Adobe Photoshop, Dreamweafer, My SQL, Apache (2.2.4) + PHP (5.2.3) . Solusi yang ingin di berikan peniliti adalah dengan merancang sistem informasi yang didukung dengan peralatan komputer berbasis web mobile. Kata Kunci : Sistem informasi Penerimaan Siswa, web mobile